1998
DOI: 10.1159/000029243
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function and Regional Distribution of Emphysema as Determined by High-Resolution Computed Tomography

Abstract: In patients with pulmonary emphysema, emphysematous changes are not uniform and vary from minimum alveolar destruction to advanced bullous formation, depending on the lobe or site in the lungs. However, we have little knowledge on whether or how this nonuniformity or localization affects pulmonary function in PE patients. Therefore, we measured the computed tomography (CT) density of divided sites in lungs with high-resolution CT images from 25 PE patients (FEV1.0%, mean ± SD 36 ± 9%, %DLCO Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 15 publications
4
40
0
3
Order By: Relevance
“…Thus, in the relatively underventilated upper lung zone, emphysema produces smaller measurable pulmonary dysfunction than in the lower zone. Consistently, GURNEY et al [67] and HARAGUSHI et al [68] showed that the extent of emphysema had higher correlations with DL,CO in the lower lung zone than in the upper lung zone, even though the upper lung zone was more severely affected by emphysema. On the basis of the lobar distribution of emphysema as determined by CT, SAITOH et al [69] reported that the airflow limitation, the RV and the TLC were higher in the predominantly lower-lobe emphysematous group than in the predominantly upper-lobe emphysematous group.…”
Section: Factors Influencing Computed Tomography Densitometrymentioning
confidence: 74%
“…Thus, in the relatively underventilated upper lung zone, emphysema produces smaller measurable pulmonary dysfunction than in the lower zone. Consistently, GURNEY et al [67] and HARAGUSHI et al [68] showed that the extent of emphysema had higher correlations with DL,CO in the lower lung zone than in the upper lung zone, even though the upper lung zone was more severely affected by emphysema. On the basis of the lobar distribution of emphysema as determined by CT, SAITOH et al [69] reported that the airflow limitation, the RV and the TLC were higher in the predominantly lower-lobe emphysematous group than in the predominantly upper-lobe emphysematous group.…”
Section: Factors Influencing Computed Tomography Densitometrymentioning
confidence: 74%
“…Mean lung density (MLD) is calculated by averaging the density of all pixels in the image that represent the entire lung. It has been validated by correlation with lung function tests [320][321][322][323]. The percentile point is defined as the cut-off density value in Hounsfield units (HU), for which a predetermined percentage of all voxels has a lower value and, as with MLD, is also influenced by density changes in all lung structures [324,325].…”
Section: Discussionmentioning
confidence: 99%
“…NAKANO et al [11] also found that core disease was related to disease severity (as measured by pulmonary function tests), with lower/core disease more related to spirometry, and upper/core to carbon monoxide transfer factor. HARAGUCHI et al [10] found that centrally distributed emphysema had the strongest relationship to pulmonary function, and also that lower-zone disease related better than upper.…”
Section: Discussionmentioning
confidence: 99%
“…Areas of the lung with a density below a given threshold (commonly -950 Hounsfield units (HU)) are designated as emphysematous. This technique has been validated against pathology [3,4] and pulmonary function [5,6]. In addition, the technology can be used to assess the distribution of emphysematous disease, an approach that has been utilised in assessing patients for (and in the outcomes of) lung volume reduction surgery [7,8] and also in monitoring changes in emphysema longitudinally in a 1 -antitrypsin-deficient patients [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation